EDIT0RIAL (American Journal of Islam and Society, 1997)
Since its inception fourteen years ago, AJZSS has built a considerablereputation as an academic Islamic journal. In addition to being a globalforum for intellectual exchange between Muslim academicians from variousdisciplines, AJZSS has contributed to efforts at Islamization ofknowledge and the reorientation of Islamic thought. And while theJournal has made sigmficant strides in reorienting Islamic thought,AJZSS cannot be the sole provider of guidance for the Islamization ofknowledge effort. Certainly, the necessary radical reorientation ofknowledge will only occur with planned coordination with other academicactivities, conferences, seminars, study circles, etc., and with thecontributions of other individuals and communities of scholars from variousparts of the world and academic disciplines.From time to time, the Journal must stress the importance of Islamicepistemology as the framework for its academic efforts. In view of ourever-developing understanding of theoretical principles drawn fromauthentic sources, and also in view of developing issues and challenges,it is important to re-examine this framework to confii that it is indeedappropriate. If the Islamic epistemology is functioning appropriately, itshould define an Islamic methodology for resemh and inquiry in all topicsand issues =levant to the Journal. All research articles should stateits methodology, which should be consistent with our system of knowledge,as well as interpret results within its own framework by using theneeded instruments and procedures for collecting and analyzing relevantdata and evidence.Although the Journal has dealt with these two themes, namely, epistemologyand methodology, they still need to be defined definitively.Muslim scholars and researchers should not just refer to Islamic epistemologyand Islamic methodology as a given or something known andunderstood; mther, they need to delve deep into the very heart of thesematters to provide more in-depth and thought-provoking contributions.We understand that many of our Muslim scholars find themselves underthe pressure of their practical circumstances when choosing theirresearch topics. In the upcoming issues, God willing, the Journal willfacilitate the endeavors of the authors to make their contributions more ...